2022
DOI: 10.5194/egusphere-2022-1395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing the chemical characteristics of Arctic low-level cloud residuals – in situ observations from a mountain site

Abstract: Abstract. The role aerosol chemical composition plays in Arctic low-level cloud formation is still poorly understood. In this study we address this issue by combining in situ observations of the chemical characteristics of cloud residuals (dried liquid cloud droplets or ice crystals) and aerosol particles from the Zeppelin Observatory in Ny-Ålesund, Svalbard (approx. 480 m a. s. l.). These measurements were part of the one-year long Ny-Ålesund Aerosol and Cloud Experiment 2019–2020 (NASCENT). To obtain the che… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…where only particles larger than around 100 nm are generally able to activate to cloud droplets. Gramlich et al (2022) came to the same conclusion by performing chemical analyses of aerosol particles and gases before, during and after cloud, without noting strong variations in chemical composition. CCN are typically associated with accumulation mode particles; however, much smaller particles can activate to cloud droplets if the supersaturations developed in clouds are high enough.…”
mentioning
confidence: 56%
“…where only particles larger than around 100 nm are generally able to activate to cloud droplets. Gramlich et al (2022) came to the same conclusion by performing chemical analyses of aerosol particles and gases before, during and after cloud, without noting strong variations in chemical composition. CCN are typically associated with accumulation mode particles; however, much smaller particles can activate to cloud droplets if the supersaturations developed in clouds are high enough.…”
mentioning
confidence: 56%
“…These cloudy periods also correspond to the time with the highest RH values, hence, this demonstrates that cloudy and wet conditions do reduce HPMTF (g) levels in the atmosphere in Svalbard during summer. However, we did not detect HPMTF nor any of its possible reaction products (e.g., C2H4SO2, C2H6SO2) (Jernigan et al, 2022) in significant amounts in any of the cloud residual samples (data not shown) (Gramlich et al, 2022). Therefore, we cannot make a conclusive statement about the fate of HPMTF in the particle phase with our dataset.…”
Section: Correlation Of Hpmtf (G) With Visibility and Relative Humiditymentioning
confidence: 55%
“…Hence, it is difficult to conclude whether the RH or air mass origin is the main reason for the lower HPMTF (g) concentration at high RH. However, during the cloud events studied in Gramlich et al (2022), HPMTF (g) levels were lower compared to right before and right after the cloudy period (Fig. 5c).…”
Section: Correlation Of Hpmtf (G) With Visibility and Relative Humiditymentioning
confidence: 86%
See 1 more Smart Citation